SPK DALAM MEREKOMENDASIKAN PESTISIDA TERBAIK UNTUK MEMBUNUH HAMA PADA TANANAMAN PADI MENGGUNAKAN METODE MAUT - Simbolon, Maria Etty; Saifullah, Saifullah; Hardinata, Jaya Tata (STMIK Budi Darma, 2019)
Pesticides are chemicals and organic which are used by farmers to protect rice plants from pests, farmers often experience difficulties in choosing the pesticides to be used. Where pesticide products circulate very much in the market and offer various advantages of each product, but often farmers experience incompatibility with what has been offered by each product Where pesticide products circulate very much in the market and offer various advantages of each product, but often farmers experience incompatibility with what has been offered by each product. The incompatibility of pesticides used by farmers can affect the yields of farmers. The purpose of this study is as knowledge of farmers in determining the best pesticides to eradicate pests in rice plants, especially in the village of Bah Sampuran and apply the MAUT method (Multi Attribute Utility Theory) to calculate each criterion of alternatives and produce cracking in recommending the best pesticides to eradicate pests in plants rice. The criteria used are: the workings of the pesticides, the price of pesticides, many pests, shelf life, the effect on humans, the influence on rice plants, the influence on other animals, climate resistance. This application was built using Vb net programming language and MySql database. From the results of this study it was found that Alternative Plenum had the highest value with a value of 0.79 so that it became the best Pesticide recommendation.Keywords: Decision Support System, Pesticides, FOREIGN, Vb net, MySql